Myths about service-oriented architecture demystifying SOA. - Anantharangachar, Raghu
Service oriented architecture (SOA) refers to an architectural solution that creates an environment in which services, service consumers and service producers can coexist, and still have no dependence on each other. SOA enables an enterprise to increase the loose coupling and the reuse of frequently used software assets. These software assets, together with the functionality that they provide, are called services in the SOA terminology. By nature, SOAs are complex and are typically applied to solutions with highly volatile requirements.